Anti-Hyperglycemic Activity of Urtica dioica Extract in Obese Male Sprague Dawley Rats: Evaluation of HOMA-IR and HOMA-β - Zaenudin Zaenudin; Jurnalis Gempaning Tyas; Kabir Ardiansyah Tangkari; Harni Sutiani; Arta Farmawati; Prasetyastuti (Universitas Muhammadiyah Surabaya, 2026)
Obesity is characterized by adipocyte accumulation that impairs glucose uptake, leading to insulin resistance, hyperglycemia, and an increased risk of diabetes mellitus. Given the limitations and adverse effects of pharmacological therapies for diabetes, alternative agents are needed. Urtica dioica contains flavonoids with anti-inflammatory and antioxidant properties that may improve glucose homeostasis. This experimental study employed a pre-test and post-test control group design using 25 male Sprague Dawley rats divided into five groups: healthy control (K1), obese control (K2), and three obese groups receiving Urtica dioica extract at doses of 125, 250, and 500 mg/kgBW (D1–D3) for four weeks. Data were analyzed using one-way ANOVA and paired t-test. Administration of Urtica dioica extract at 500 mg/kgBW (D3) significantly reduced blood glucose (79.90 ± 2.51 vs. 177.92 ± 3.30; p<0.05), increased insulin levels (16.20 ± 0.29 vs. 12.82 ± 0.28; p<0.05), decreased HOMA-IR (3.19 ± 0.07 vs. 5.63 ± 0.14; p<0.05), and enhanced HOMA-β (351.20 ± 58.77 vs. 40.21 ± 1.63; p<0.05) compared with untreated obese controls. In conclusion, four-week administration of Urtica dioica extract effectively improved insulin resistance and β-cell function in obese rats, with the most pronounced effect observed at a dose of 500 mg/kgBW.